El gasto ejecutado y la asignación presupuestal de la municipalidad provincial de Loreto Nauta periodo 2019 – 2023 - Vargas Machuca Sifuentes, Leysi Angelica (2025)
Public institutions frequently state that the budget allocated per year is not sufficient to carry out the planned activities and works and request its expansion. However, the Ministry of Economy and Finance - MEF argues that they do not execute the entire budget and revert to the public treasury. That is why this master's thesis is carried out with the objective of analyzing the expenditure executed and the budget allocation of the Provincial Municipality of Loreto Nauta in the period 2019 - 2023. This thesis is of Quantitative type, Descriptive level and Non-Experimental design. the following conclusions are reached: The budget execution of the Municipality reached 59.12% of the assigned budget, during the period 2019 - 2023. The budget execution by generic expenditure item is concentrated in the concept Acquisition of Non Financial Assets, with an amount of S/. 194,894,758.69; equivalent to 64.23% of the total expense. The study of the financing sources of the budget assigned to the Provincial Municipality of Loreto Nauta shows that the largest contribution came from Resources for Credit Operations, which reached S/. 192,808,284.00 meaning 37.57% of the total. The second source with the greatest contribution was Ordinary Resources with S/. 167,401,378.00; equal to 32.62%. The amount of the allocated budget varied from one year to the next, with increases and reductions.